Sisters of the Lost Marsh - Strange, Lucy. (New York : Chicken House, Scholastic Inc., 2023)
Living in fear of their father, six cursed sisters sneak out to visit Full Moon Fayre, but when Grace, the oldest sister, goes missing, they must battle inner doubts and the legends that have haunted their family to save her.
Includes bibliographical references.
Booklist
Kirkus Starred
Pub Weekly
Booklist, December 2022
Kirkus Starred, December 2022
Keywords: Blessing and cursing -- Juvenile fiction; Farms -- Juvenile fiction; Marshes -- Juvenile fiction; Missing persons -- Juvenile fiction; Secrecy -- Juvenile fiction; Sisters -- Juvenile fiction; Blessing and cursing -- Fiction; Farms -- Fiction; Marshes -- Fiction; Missing persons -- Fiction; Secrets -- Fiction; Sisters -- Fiction; Blessing and cursing -- Fiction; Farms -- Fiction; Marshes -- Fiction; Missing persons -- Fiction; Secrecy -- Fiction; Sisters -- Fiction; Historical fiction